2014
DOI: 10.12788/jcso.0095
|View full text |Cite
|
Sign up to set email alerts
|

Information and communication needs of Chinese American breast cancer patients: perspectives on survivorship care planning

Abstract: Background The existing knowledge on the survivorship experiences of Chinese American breast cancer survivors (CABCS) has arisen largely from aggregated data across multiethnic or multicancer studies that have focused on quality of life. Little is known about Chinese American perspectives and preferences for survivorship care. Objective To examine the experiences of CABCS to better understand their information and communication needs and their preferences for survivorship care plans (SCPs). Methods 16 CABC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
85
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(86 citation statements)
references
References 27 publications
1
85
0
Order By: Relevance
“…However, challenges in addressing these elements of post-treatment care in a safety-net setting with non-English speaking and limited English proficiency (LEP) breast cancer patients has received little attention. A recent study of SCP preferences among Chinese American breast cancer survivors found that the women interviewed would prefer reviewing the treatment summary in person with a provider, and that follow up written information in lay language in English and Chinese would be acceptable [11]. Preferred content was similar to that identified in the data presented herein, with the addition of requests for information on Traditional Chinese Medicine.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…However, challenges in addressing these elements of post-treatment care in a safety-net setting with non-English speaking and limited English proficiency (LEP) breast cancer patients has received little attention. A recent study of SCP preferences among Chinese American breast cancer survivors found that the women interviewed would prefer reviewing the treatment summary in person with a provider, and that follow up written information in lay language in English and Chinese would be acceptable [11]. Preferred content was similar to that identified in the data presented herein, with the addition of requests for information on Traditional Chinese Medicine.…”
Section: Discussionmentioning
confidence: 85%
“…Further, they argue that the emerging science and implementation of SCPs are void of patient input. Overall, this research suggests gaps in the ability of existing SCP templates to address the information needs of specific population groups or to be particularly useful to patients as they transition from oncology to primary care [11–14]. The study reported here is the first that we are aware of that includes perspectives of ethnically and linguistically diverse safety-net breast cancer patients on SCP content and delivery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, advanced nurse practitioners may be best placed to facilitate this and encourage discussion about and uptake of both SCPs and ACP in these older cancer survivors, particularly when frailty and multimorbidity are recognised [54,62]. Personal (face-to-face) contact with trained staff is acceptable and preferable to many patients [63] and has been shown to improve adherence with SCPs [16]. Thus, it could be a useful format for delivering ACP where desired.…”
Section: Search Strategy and Selection Criteriamentioning
confidence: 99%
“…Outreach to underserved minority groups such as Asian Americans requires the understanding of their common health disparities as well as an appreciation of known barriers such as acculturation, which can influence their access to care and perception of health. 7,8 Of the top 6 largest US Asian groups (Japanese, Korean, Asian Indian, Filipino, Vietnamese, and Chinese), Chinese Americans lead the US Asian population, representing just over 4 million people (23.2%). 9 The Chinese also lead this group in rising poverty rates, reaching 15.2% in 2012.…”
Section: Introductionmentioning
confidence: 99%